2015
DOI: 10.1002/adma.201502916
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Negative Capacitance in Multidomain Ferroelectric–Paraelectric Nanocapacitors at Finite Bias

Abstract: The emergence of negative capacitance in an ultrathin ferroelectric/paraelectric bilayer capacitor under electrical bias is examined using first-principles simulation. An antiferroelectric-like behavior is predicted, and negative capacitance is shown to emerge when the monodomain state becomes stable after bias application. The polydomain-monodomain transition is also shown to be a source of capacitance enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…4a. It has been reported that 180°out-of-phase ferroelectric multi-domains are favorable for the reduction of stray fields in ferroelectric layers 35,36 . (The stability of ferroelectric multi-domains is…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4a. It has been reported that 180°out-of-phase ferroelectric multi-domains are favorable for the reduction of stray fields in ferroelectric layers 35,36 . (The stability of ferroelectric multi-domains is…”
Section: Discussionmentioning
confidence: 99%
“…d Schematic diagram of the effective ferroelectric-induced electromotive force (emf) originating from ferroelectric polarization switching. This effective ferroelectric-induced emf behaves like the emf predicted by Lenz's law, which opposes the applied electric field and so contributes to the inductance of the ferroelectric layer discussed in Supplementary Information, Note 11.) Hence, the polarizations in ferroelectric multi-domains are organized with alternate up and down orientations 35,36 . The DC bias generates a net polarization in ferroelectric multi-domains.…”
Section: Discussionmentioning
confidence: 99%
“…When the charge compensation is fluent in case of MFM, L crit is of the order of atomic dimension. Even with the epitaxial SrTiO 3 /BaTiO 3 of the first‐principles calculation by Kasamatsu et al, where the SrTiO 3 was ≈5 unitcell thick (≈2 nm), lateral BaTiO 3 domains with two‐unitcell width was still stable compared with the depoled state. Therefore, L crit is ≈1 nm in the perovskite FE materials, which is consistent with the recent expectation by Hoffmann et al…”
Section: Stabilization Of Nc By Scaling Device Dimensionsmentioning
confidence: 94%
“…The negative capacitance (NC) effect using the suppression of the spontaneous polarization of the ferroelectric (FE) material is now attracting a great deal of interest as a strategy to achieve extremely large capacitance density or the subthreshold swing of sub‐60 mV per decade in field effect transistors . The capacitance enhancement in the ferroelectric/dielectric (FE/DE) bilayer larger than the capacitance of the constituent DE layer was suggested as an evidence of the occurrence of the static NC effect in the FE/DE bilayer system, which was first reported in the epitaxial‐Pb(Zr 0.2 Ti 0.8 )O 3 /SrTiO 3 (PZT/STO) capacitor at a temperature higher than 573 K in 2011 .…”
Section: Introductionmentioning
confidence: 99%